2011
DOI: 10.1007/s00134-011-2394-y
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the time-course of ventilator-induced lung injury: what can we learn from interspecies discrepancies?

Abstract: Alterations in lung fluid balance, increases in endothelial and epithelial permeability, and severe tissue damage have been widely described in animals following injurious mechanical ventilation and regrouped under the term ventilator-induced lung injury (VILI) [1]. The clinical relevance of VILI was highlighted by the acute respiratory distress syndrome (ARDS) Network trial that showed a 22% reduction of mortality in patients with ARDS when the mechanical stress applied to the lungs was lessened by reducing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…A s a life-saving therapy, the majority of patients with acute respiratory distress syndrome (ARDS) require mechanical ventilation to support the failing lungs, but this in turn raises the risk of ventilator-induced lung injury (VILI) (1). Reducing tidal volume (Vt) improves both mortality and morbidity (2-4).…”
Section: Influence Of Inspiration To Expirationmentioning
confidence: 99%
“…A s a life-saving therapy, the majority of patients with acute respiratory distress syndrome (ARDS) require mechanical ventilation to support the failing lungs, but this in turn raises the risk of ventilator-induced lung injury (VILI) (1). Reducing tidal volume (Vt) improves both mortality and morbidity (2-4).…”
Section: Influence Of Inspiration To Expirationmentioning
confidence: 99%
“…It was concluded that lung strain may play a critical role as a unifying rule describing the development of VILI among mammals with healthy lungs. This article is accompanied by an editorial comment by de Prost et al [29]. …”
Section: Mechanical Ventilationmentioning
confidence: 99%